A graduação em medicina: um olhar reflexivo sobre o aprendizado e a análise crítica da literatura durante a pandemia de COVID-19 - Tofanelli, Laisa Prandine (Universidade Federal de São Carlos, 2024)
During the COVID-19 pandemic, concerns arose about the risk of generating aerosols and transmitting SARS-CoV-2 to healthcare professionals during airway management procedures. These are primary interventions in the care of critically ill patients, with no possibility of suspension or postponement. In this context, several technologies have been proposed to reduce the risk of transmission of respiratory infections in hospital and out-of-hospital health services. Objectives: To evaluate the effectiveness and adverse effects of new technologies and procedures for obtaining an advanced airway in preventing the transmission of respiratory infections to healthcare professionals and patients. Materials and methods: This systematic review compared new technologies and procedures with traditional techniques in situations in which adult patients (≥18 years) underwent procedures to obtain an advanced airway, covering searches in the Medline, Embase and Web of Science databases in English, Portuguese and Spanish. The selected studies were assessed for risk of bias using the ROBINS-I, ROBINS-E and RoB 2 tools. Results: 1279 non-duplicate articles were identified, 57% of the studies being produced during the pandemic period. Three studies were selected for the systematic review, two cohort studies and one open randomized clinical trial. Many studies were excluded because they used new techniques that were not tested on real patients or without a comparative control group. There was no evidence that modifications to advanced airway procurement protocols altered the risk of SARS-CoV-2 transmission, nor that they were associated with a greater occurrence of adverse events. However, the selected articles were classified as having a high risk of bias. There was also a technical challenge in directly measuring the reduction in the risk of healthcare professionals contracting respiratory infections during procedures, both due to difficulty in documenting proven infection and because it was not possible to exclude other sources of infection. Discussion: There was great scientific production in the period, but with methodological limitations in the studies identified. The pandemic was a factor that stimulated scientific production, but limited the quality of evidence. The abundance of studies proposing new techniques was not accompanied by comparative effectiveness studies in terms of reducing SARS-CoV-2 transmission, making it impossible to assess their clinical usefulness. Conclusion: The pandemic stimulated the development of new techniques and procedures to ensure safety in obtaining an advanced airway. However, these methodologies still need to be evaluated regarding their effectiveness and safety, in addition to the costs of their incorporation into clinical practice.
Graduation in medicine: a reflective look at the learning and critical analysis of literature during the pandemic of COVID-19
Keywords: Intubação; Manuseio das vias aéreas; Adulto; Equipamentos de proteção; Eficácia; Segurança; Revisão sistemática; COVID-19; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA